Realization of an Interactive Education Model Using the Means of Information and Communication Technologies at a Technological University - Pokidov, Mikhail Gerasimovich; Pokidov, Boris Mikhailovich; Khryuchkina, Elena Alexeevna; Shkurat, Petr Alexandrovich; Shkurat, Petr Alexandrovich; Skripkin, Ivan Nikolaevich (International Journal of Psychosocial Rehabilitation, 2020)
One trend of modern education is its informatization, which provides the use of interactive learning means. Therefore, the aim of this study is to analyze the interactive means of teaching political science as a means to enhance the educational and cognitive activities of students. The experimental work was realized in political science lectures with students of experimental and control groups. Based on the data obtained, it can be concluded about the effectiveness of the use of interactive means of teaching political science in a technological university.